Sustainable social tourism in Colombia: the link between social entrepreneurship and sustainability - González Cortés, Luz Dary; Talero Soraya, Husain (2021)
Sustainable tourism is defined as "tourism that takes full account of its current and future economic, social and environmental impacts, addressing the needs of visitors, the industry, the environment and host communities"(UNWTO, 2015). It is considered a key element for development, as stated by Ateljeciv & Page (2009), particularly in developing countries such as Colombia that possess numerous attributes, both natural and cultural, and at the same time a multidimensional poverty of 17%, with 7.4% of the population living under extreme poverty conditions (DANE, 2017). Therefore, sustainable tourism is considered a way in which the unmet needs of society can be satisfied, keeping in mind present and future generations (Husain-Talero, 2016).